2008
DOI: 10.1097/ico.0b013e3181583115
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Endothelial Cell Loss After Cataract Extraction by Using Ultrasound Phacoemulsification Versus a Fluid-based System

Abstract: Our study showed significantly lower ECL after phacoemulsification for a fluid-based versus an ultrasound system. The fluid-based method was safer than conventional ultrasound in cataract surgery, with a nuclear opalescence graded up to 4.9 in the LOCS III classification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 28 publications
2
38
0
Order By: Relevance
“…24 In contrast, pseudophakic bullous keratopathy (PBK) is an acquired corneal endothelial disorder that may occur following intraocular cataract extraction surgery. 25 Various causative factors such as excessive phacoemulsification energy 26 and mechanical trauma 27 to the corneal endothelium during cataract extraction surgery have been implicated in causing stress-induced apoptosis of CECs. 28 Although PBK is characterized by diffuse damage to the corneal endothelial layer, 29 a peripheral rim of healthy CECs and DM is usually retained in corneas affected by FED.…”
mentioning
confidence: 99%
“…24 In contrast, pseudophakic bullous keratopathy (PBK) is an acquired corneal endothelial disorder that may occur following intraocular cataract extraction surgery. 25 Various causative factors such as excessive phacoemulsification energy 26 and mechanical trauma 27 to the corneal endothelium during cataract extraction surgery have been implicated in causing stress-induced apoptosis of CECs. 28 Although PBK is characterized by diffuse damage to the corneal endothelial layer, 29 a peripheral rim of healthy CECs and DM is usually retained in corneas affected by FED.…”
mentioning
confidence: 99%
“…The insignificant endothelial cell loss of 4.1% in this group is quite low when compared to other studies on phacoemulsification which have shown endothelial losses ranging from 4 to 25% [4,21,22,23,24,25,26]. …”
Section: Discussionmentioning
confidence: 72%
“…There is a study by Richard et al [4] that suggests that Aqualase has a less deleterious effect on the corneal endothelium than phacoemulsification. One month after surgery, the corneal endothelial loss was 24.3% in the phacoemulsification group versus only 11.2% in the Aqualase group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations